THE INFLUENCE OF DIGITAL FINANCIAL LITERACY ON STUDENT FINANCIAL BEHAVIOR IN THE DIGITAL ECONOMY ERA - Syahrial Hasanuddin Pohan; Nova Yanti Maleha; Muhammad Naihul Author (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to examine the influence of digital financial literacy on students' financial behavior in the digital economy era thru a literature review approach. Digital financial literacy is defined as the ability to access, understand, and utilize technology-based financial information for sound financial decision-making. This study collected data from journal articles, books, and official reports published in the last ten years, which were then analyzed using thematic analysis and narrative synthesis methods. The study results indicate that students with high levels of digital financial literacy tend to exhibit healthy financial behaviors, such as budgeting, controlling spending, saving, and investing systematically. Conversely, low digital financial literacy is associated with consumerist behavior, impulsive buying, and low awareness of the security of personal financial data. This finding underscores the importance of digital financial literacy education and training strategies for students to cultivate sustainable financial behavior amidst the increasingly rapid advancements in financial technology.